On Soft Strongly Ƅ*-Separation Axioms - Hameed, Saif Z.; Radwan, Abdelaziz E.; El-Seidy, Essam (Iraqi Journal of Science, 2024)
In this paper, we study some new types of soft separation axioms called soft strongly Ƅ*-separation axioms. We show that, the properties of soft strongly Ƅ*-T_i  space (i =0, 1,2) are soft topological properties under the bijection, soft irresolute and soft continuous mapping. Furthermore, the property of being soft strongly Ƅ*-regular and soft strongly Ƅ*-normal are soft topological properties under bijection, soft continuous functions.  Moreover, their relationships with existing spaces are studied.